Proteasomes and Ubiquitin C-Terminal Hydrolase L1 as Biomarkers of Tissue Damage and Inflammatory Response to Different Types of Injury—A Short Review - Marzena Tylicka; Ewa Matuszczak; Joanna Kamińska; Beata Modzelewska; Olga Martyna Koper-Lenkiewicz (Life)
The proteasomal system of protein degradation is crucial for various cellular processes, including transduction of signals and differentiation of cells. Proteasome activity rises after various traumatic stressors such as hyperoxia, radiation, or oxidative damage. Removal of damaged proteins is essential to provide the necessary conditions for cell repair. Several studies report the activation of the proteasomal degradation system after thermal injury, CNS injury, abdominal trauma, ischemia-reperfusion injury, and possible clinical implications of the use of proteasome inhibitors. It is important to highlight the distinct and crucial roles of UCHL1, 26S, and 20S proteasome subunits as biomarkers. UCHL1 appears to be particularly relevant for identifying brain and neuronal damage and in advancing the diagnosis and prognosis of traumatic brain injury (TBI) and other neurological conditions. Meanwhile, the 26S and 20S proteasomes may serve as markers for peripheral tissue damage. This differentiation enhances our understanding and ability to target specific types of tissue damage in clinical settings.